Detection of bacteria from local vegetables by pcr-rflp of mitocondrial dna (mtDNA) 16S rRNA - Shahidan, Siti Hawa (Universiti Sains Malaysia, 2016)
Foodbome disease is one of the growing public health problems occurred worldwide including Malaysia. The common causes of foodborne disease are due to microorganisms, chemical and bio-toxin which are found in raw or lightly cooked vegetables. In this study, ten local vegetables, namely spinach (bayam), water spinach (kangkong), white flowering cabbage (sawi manis), Chinese broccoli (kailan), cabbage (kobis), tomato (tomato), sweet potato (keledek), eggplant (terung), long beans (kacang panjang) and chili (cili) were selected for the identification of bacteria through PCRRFLP of mitochondrial 16S rRNA gene. A new primer was designed based on mitochondrial 16S rRNA gene sequences of selected bacteria, such as Pseudomonas syringae, Pseudomonas protegens, Listeria monocytogenes, Salmonella enterica, Erwinia amylovora. Erwinia carotovora. Bacillus cereus. Bacillus subtilis, Bacillus licheniformis and Escherichia coli. A partial sequence of 16S RrNA gene was PCR amplified and digested by endonuclease enzymes Alu 1, Hha 1, Hae 111 and EcoR 1. Identification of bacteria was assigned based on species-specific variation pattern produced from digested product.